Acute symptomatic hyponatremia in setting of SIADH as an isolated presentation of COVID-19 - Habib, Mhd Baraa (IDCases, 2020)
The syndrome of inappropriate secretion of antidiuretic hormone (SIADH) is one of the most common causes of hyponatremia in hospitalized patients. Wide spectrum of etiologies associated with hyponatremia pose significant challenges in detecting and treating this disorder. Several infectious causes of SIADH have been reported; however, hyponatremia associated with SIADH and Coronavirus disease 2019 (COVID-19) was only recently mentioned in a few case reports. We discuss a unique presentation of COVID-19, in which the patient presented with acute severe symptomatic hyponatremia thought to be the initial and isolated presentation of SARS-CoV-2 infection.